Attitude towards mathematics from parents of secondary students - Meza-Cascante, Luis Gerardo; Suárez-Valdés-Ayala, Zuleyka; Agüero-Calvo, Evelyn; Calderón-Ferrey, Martha; Jiménez-Céspedes, Rodolfo; Sancho-Martínez, Laura; Pérez-Tyteca, Patricia; Monje-Parrilla, Javier (Uniciencia, 2021)
The main objective of the paper was to study the level of attitude parents of Costa Rican regular secondary school students have towards mathematics, by analyzing differences between sex, levels of education, and age ranges. This paper is a quantitative descriptive exploratory research. The sample consisted of 1851 parents of Costa Rican public, academic, and daytime secondary school students. The design was a stratified simple random sample, based on the location (rural or urban) and the geographical area (province) students were in when enrolled in 2019. In addition, the statistical techniques applied to study the research hypotheses are Student’s t-distribution and one-way ANOVA. As a result, it is inferred that there are differences between men and women in their level of attitude towards mathematics, showing the first higher levels with low effect size. There were also differences between parents with incomplete primary or secondary education with those who completed college, the latter showing higher levels of attitude. Differences were also detected in the attitude towards mathematics between people ages 35-50 with those older, with low effect size. It is concluded that 75.6 % of the surveyed parents showed high levels of attitude towards mathematics, which is a positive finding.